-(v-2)=-4(v-8)-8v

Simple and best practice solution for -(v-2)=-4(v-8)-8v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(v-2)=-4(v-8)-8v equation:


Simplifying
-1(v + -2) = -4(v + -8) + -8v

Reorder the terms:
-1(-2 + v) = -4(v + -8) + -8v
(-2 * -1 + v * -1) = -4(v + -8) + -8v
(2 + -1v) = -4(v + -8) + -8v

Reorder the terms:
2 + -1v = -4(-8 + v) + -8v
2 + -1v = (-8 * -4 + v * -4) + -8v
2 + -1v = (32 + -4v) + -8v

Combine like terms: -4v + -8v = -12v
2 + -1v = 32 + -12v

Solving
2 + -1v = 32 + -12v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '12v' to each side of the equation.
2 + -1v + 12v = 32 + -12v + 12v

Combine like terms: -1v + 12v = 11v
2 + 11v = 32 + -12v + 12v

Combine like terms: -12v + 12v = 0
2 + 11v = 32 + 0
2 + 11v = 32

Add '-2' to each side of the equation.
2 + -2 + 11v = 32 + -2

Combine like terms: 2 + -2 = 0
0 + 11v = 32 + -2
11v = 32 + -2

Combine like terms: 32 + -2 = 30
11v = 30

Divide each side by '11'.
v = 2.727272727

Simplifying
v = 2.727272727

See similar equations:

| x(x+3)=-8 | | (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= | | 6a-18b+12c= | | 12a-28b+10c= | | 40=5w-15 | | 7x-7y-7z= |

Equations solver categories